Pendekatan Teori Himpunan untuk Pemetaan Segmentasi Minat Pengguna pada Algoritma For You Page (FYP) TikTok - Abdillah, Zidan; Artika Lestari, Desti; Al Zaidan, Hilmi; Ramdhani Arrahman, Rizki; Lutfiyah, Aini; Ramadhan, Rizky; Malik Al Saleh, Sultan; Putri Zulkarnain, Nania; Sulistyani, Anjar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The massive growth of the TikTok platform is driven by the sophistication of its For You Page (FYP) algorithm, which performs real-time, interest-based content personalization. This phenomenon creates complexity in audience segmentation due to the high overlap of preferences among users. This study aims to formulate a logical-mathematical framework using Set Theory as a formal instrument to identify, map, and analyze the relationships between TikTok user interest segments through a literature review method. The modeling results show that the concepts of universal set, subset, and basic operations such as intersection, union, difference, complement, and cardinality can be effectively transformed into a precise audience segmentation model. The intersection operation identifies niche audiences, the union operation maps the accumulation of broad market reach, and the difference operation functions as an exclusion-list filtering mechanism. This study contributes theoretically through an interdisciplinary synthesis between discrete mathematics and social communication science, and practically as a strategic guide for digital marketers and content creators optimizing message-distribution targeting on social media.